8
$\begingroup$

Why is it that $$ \left(1+\frac{1}{n}\right)^n < \left(1+\frac{1}{m}\right)^{m+1}, $$ for any natural numbers $m, n$?

I have tried expanding using the binomial series and splitting into cases. I understand why it is trivially true when $m=n$ but I am not sure if there is a rigorous proof for other cases?

$\endgroup$
7
$\begingroup$

Both sequences $$ a_n=\left(1+\frac{1}{n}\right)^n, \quad b_n=\left(1+\frac{1}{n}\right)^{n+1} $$ are monotonic. In particular, $a_n$ is increasing and $b_n$ is decreasing.

Hence, if $m,n\in \mathbb N$ and $k=$max$\{m,n\}$, then $$ a_n\le a_k\le b_k\le b_m. $$

Why are these sequences monotonic?

We have $$ \frac{a_{n+1}}{a_n}=\frac{(n+2)^{n+1}n^n}{(n+1)^{2n+1}}=\frac{n+2}{n+1}\cdot\left(\frac{n^2+2n}{(n+1)^2}\right)^n \\ =\frac{n+2}{n+1}\cdot\left(1-\frac{1}{(n+1)^2}\right)^n \ge \frac{n+2}{n+1}\cdot\left(1-\frac{n}{(n+1)^2}\right)=\frac{(n+2)(n^2+n+1)}{(n+1)^3}=\frac{n^3+3n^2+3n+2}{n^3+3n^2+3n+1}>1. $$ In a similar fashion we get that $b_n$ is decreasing: $$ \frac{b_n}{b_{n+1}}=\frac{\left(1+\frac{1}{n}\right)^{n+1}}{\left(1+\frac{1}{n+1}\right)^{n+2}}=\frac{(n+1)^{2n+3}}{n^{n+1}(n+2)^{n+2}}=\frac{n+1}{n+2}\cdot \left(\frac{n^2+2n+1}{n^2+2n}\right)^{n+1} \\ = \frac{n+1}{n+2}\cdot \left(1+\frac{1}{n^2+2n}\right)^{n+1}\ge \frac{n+1}{n+2}\cdot \left(1+\frac{n+1}{n^2+2n}\right) =\frac{(n+1)(n^2+3n+1)}{(n+2)(n^2+2n)}=\frac{n^3+4n^2+4n+1}{n^3+4n^2+4n}>1. $$

| cite | improve this answer | |
$\endgroup$
  • $\begingroup$ S. Symliris Interesting! $\endgroup$ – Z Ahmed Jan 17 at 8:43
  • $\begingroup$ Yiorgos.Nice answer. To show that $b_k$ is decreasing is a bit tricky. math.stackexchange.com/questions/2071492/…. If this is proven, and knowing that $\lim a_n=e=\lim b_m$ $a_n\le e \le b_m$, the answer is obvious. $\endgroup$ – Peter Szilas Jan 17 at 9:38
2
$\begingroup$

The inequality holding for all naturals implies that

$$\left(1+\frac{1}{n}\right)^n < L\le U < \left(1+\frac{1}{m}\right)^{m+1},$$

where $U=\inf_m\left(1+\dfrac{1}{m}\right)^{m+1}, L=\sup_n\left(1+\dfrac{1}{n}\right)^n $. There may not be any overlap between the values in the LHS and RHS.


Indeed for all real $x>0$, $$\left(1+\frac1x\right)^x<e$$ and $$\left(1+\frac1x\right)^{x+1}>e.$$

Both functions are monotonic and their limit $x\to\infty$ is $e$.


Monotonicity follows from the inequalities

$$\frac1{x+1}<\log\left(1+\frac1x\right)<\frac1x$$ which imply positive and negative derivatives respectively. These inequalities are supported by inequalities between the derivatives

$$-\frac1{(x+1)^2}>-\frac1{x(x+1)}>-\frac1{x^2}$$ and the common value $0$ at infinity.

| cite | improve this answer | |
$\endgroup$
  • $\begingroup$ Sorry, @Yves Daoust I wanted to help. :) $\endgroup$ – Michael Rozenberg Jan 17 at 8:39
  • $\begingroup$ @MichaelRozenberg: no problem, but the inequalities hold in all positives, and there was a typo in the directions. $\endgroup$ – Yves Daoust Jan 17 at 8:40
  • $\begingroup$ Very interesting $\endgroup$ – Z Ahmed Jan 17 at 8:41
1
$\begingroup$

For a simple answer to why is $\left(1+\frac{1}{n}\right)^n < \left(1+\frac{1}{m}\right)^{m+1}$? -- it is because of the inequality of geometric and arithmetic means. In particular

$a_n = \big(1 + \frac{1}{n}\big)^n \lt \big(1 + \frac{1}{n+1}\big)^{n+1} = a_{n+1}$
or equivalently, taking n+1 th roots
$a_{n}^\frac{1}{n+1}= \big(1 + \frac{1}{n}\big)^\frac{n}{n+1} = \big(1 + \frac{1}{n}\big)^\frac{n}{n+1}\cdot 1^\frac{1}{n+1} \lt \frac{n}{n+1}\big(1 + \frac{1}{n}\big) + \frac{1}{n+1}\big(1\big) = 1 + \frac{1}{n+1} = a_{n+1}^\frac{1}{n+1}$
by $\text{GM}\leq \text{AM}$ (which holds with equality iff all items in the geometric mean are identical)

and by the same manipulation we get $c_r = \big(1 - \frac{1}{r}\big)^r \lt \big(1 + \frac{1}{r+1}\big)^{r+1} = c_{r+1}$

so $a_n$ and $c_r$ are strictly monotone increasing

For the question posed: by monotone behavior of $a_n$, if $n \leq m$ then we automatically have
$(1+\frac{1}{n})^n \leq (1+\frac{1}{m})^{m}\lt (1+\frac{1}{m})^{m}\cdot (1+\frac{1}{m}) = (1+\frac{1}{m})^{m+1}$

it remains to consider the case of $m \lt n$. In this case we can divide out $(1+\frac{1}{m})^{m+1}$ and prove the equivalent

$\left(1+\frac{1}{n}\right)^n \left(1-\frac{1}{m+1}\right)^{m+1} = \left(1+\frac{1}{n}\right)^n \left(\frac{m}{m+1}\right)^{m+1}=\left(1+\frac{1}{n}\right)^n \left(1+\frac{1}{m}\right)^{-(m+1)}\lt 1 $

but
$\left(1+\frac{1}{n}\right)^n \left(1-\frac{1}{m+1}\right)^{m+1} \leq \left(1+\frac{1}{n}\right)^n \left(1-\frac{1}{n}\right)^{n}\lt 1$
by the monotone behavior of $c_r$ and $\text{GM}\leq \text{AM}$ which proves the claim

note: if you don't like splitting this into 2 cases, then the claim is proven directly by considering monotone behavior in $a_n$ and $c_r$, and for any $m,n$ select natural number $k \gt \max(m+1,n)$ and the direct proof is

$\left(1+\frac{1}{n}\right)^n \left(1-\frac{1}{m+1}\right)^{m+1} \lt \left(1+\frac{1}{k}\right)^k \left(1-\frac{1}{k}\right)^{k}\lt 1$

and of course
$\left(1+\frac{1}{k}\right)^k \left(1-\frac{1}{k}\right)^{k}\lt 1$ is equivalent to proving the claim with 2kth roots of each side but

$\left(1+\frac{1}{k}\right)^\frac{1}{2} \left(1-\frac{1}{k}\right)^\frac{1}{2}\lt \frac{1}{2}\left(1+\frac{1}{k}\right)+ \frac{1}{2}\left(1-\frac{1}{k}\right) = 1$ by $\text{GM}\leq \text{AM}$

| cite | improve this answer | |
$\endgroup$

Your Answer

By clicking “Post Your Answer”, you agree to our terms of service, privacy policy and cookie policy

Not the answer you're looking for? Browse other questions tagged or ask your own question.